Вы находитесь на странице: 1из 23

3 · 10 8

3 · 10 8

0 µ 0 z S C τ C

• 3 · 10 8 3 · 10 8 ♣ • • 0 µ 0 z

n n] C =

zˆ × τ

E(r, t)

=

H(r, t) =

E(r)e jωt =

(e t (x, y) + e z (x, y)zˆ ) e j(ωtβz)

H(r)e jωt =

(h t (x, y) + h z (x, y)zˆ ) e j(ωtβz)

E(r) H(r) E(r, t) H(r, t)

E H 2 E

2 E µ 0 0

2 H µ 0 0

= 0

∂t 2 2 H

∂t 2

= 0

E · τ] C = 0

H · n] C = 0

z

e z h z S

2

t

2

t

2

e z + (k h z + (k

0

2

0

β 2 )e z = 0

β 2 )h z = 0

t = ∇ − z zˆ k 0 = ω 0 µ 0 = ω

c

E H

e t

h t

=

=

1

β 2 [jωµ 0 zˆ × ∇ t h z t e z ]

2

k

0

1

β 2 [ 0 zˆ × ∇ t e z + t h z ]

k

2

0

e z ] C

n · ∇ t h z ] C

=

=

0

h z

∂n

C

 

= 0

e z h z e t

h t E H

e z = 0

S

2

h z + k

t

2

c

h z = 0

h z

∂n

C

= 0

h z

k

β 2 e t h t

2

c

= k

2

0

e t

h

t

=

=

jωµ β 2 zˆ × ∇ t h z 0

0

2

k

jβ β 2 t h z 0

2

k

e z = 0

S

2

e z + k

t

2

c

e z = 0

e z ] C = 0

e z k e t h t

2

c

jβ

e t

β 2 t e z

=

k

2

0

h t

=

jω 0 β 2 zˆ × ∇ t e z

k

2

0

e z = h z = 0

e z = h z = 0

S

t × e t (x, y) =

0

t · e t (x, y) = 0

e t (x, y) = −∇ t φ(x, y)

2

φ(x, y) = 0

t

φ(x, y)] C = K

=

φ(x, y)] S

K

e t ] S

=

−∇ t φ] S = 0 h t = 0

mn

2 h z + 2 h z

∂x 2

∂y 2

+ k

2

c

h z = 0

∂h z

∂x

∂h z

∂y

x=0

y=0

∂h z

∂x

∂h z

∂y

x=a

=

= y=b

=

= 0

z ∂x ∂h z ∂y x = a = = y = b = = 0

h z,mn (x, y) = A TE cos mπx cos nπy

mn

a

m, n = 0, 1, 2, 3,

b

m = n

= 0

k TE

c,mn 2 = mπ

a

2 +

b

2

h z,mn k c,mn 2

mn

TE

k

2

0

β

TE

mn

2 = 2 +

a

b

2

β

TE

mn =

ω

c

2 2

a

b

2

> c mπ

a

2 +

b

2 β

mn

mn

mn

ω

TE

mn

ω < c mπ

a

2 +

b

2 β

TE

mn

c,mn = c

f TE

m

2a 2 + 2b 2

n

mn

2 e z + 2 e z

∂x 2

∂y 2

+ k

2

c

e z = 0

e z ] x=0 =

e z ] x=a = e z ] y=0 =

e z ] y=b = 0

e z,mn (x, y)

= A TM mπx nπy

a

mn

b

m, n = 1, 2, 3,

k TM

c,mn 2 = mπ

a

2 +

b

2

mn mn

mn

c,mn = c

m

2a 2 + 2b 2

n

f TM

β

f c1

f c2

f c1 < f < f c2

1,25f c1 < f < 0,95f c2

β ω

10 f c1 = 2a a > 2b

20 f c2 = a = 2f c1

a = 2,286 b = 1,016 f c1 = 6,562

f c2 = 13,123

f 10,5

c

c

0 < f < f c1

10

E H

E

H

jωµ 0 a

π

A

TE

10

TE

10

πx yˆ e jβ

a

a

πx xˆ +

a

TE

10

z

=

cos πx zˆ e jβ

a

= A TE

10

π

TE

10

z

f

TE

c,10 =

2a c

β

TE

10

λ

TE

g,10

=

=

ω

c

2 π

a

2

2π

c

β

TE

10

=

f 2 f

c,10 2

TE

E

= ωµ 0 a

2π

A

TE

10

e j ( β

TE

10

z+ πx

a

)

e j ( β

TE

10

zπx

a

 

) yˆ

k + = π xˆ +β

k = π xˆ

zˆ

10

k + k

TE

10

zˆ

a

+ β

TE

10

a

) y ˆ k + = π x ˆ + β k − = − π

θ

z

TE

cos θ = |k β + |

10

=

β

TE

10

β

TE

10

2 + π

a

2 =

1 f

f

TE

c,10

2

z

ω

c

c

v p =

β

TE

10

=

1 f

TE

c,10

f

2 = cos θ

> c

c z

v g = c cos θ = c

1 f

f

TE

c,10

2

< c

10

10

v g =

1

TE

10

10 +z

10 +z

10 z

• 1 0 + z 1 0 + z 1 0 − z 1 0 E

10

E

=

jωµ 0 a

π

A

TE

10

πx yˆ e jβ

a

TE

10

z 1 + Γ L e 2jβ

TE

10

(z 0)

z

Γ L

x = a E x

2

E(x = a , z)

2

=

jωµ 0 a

C

TE

10

TE

10

yˆ e jβ

TE

10

1 + Γ L e 2jβ

TE

10

z

A

z

π

yˆ e jβ

TE

10

z 1 + Γ L e 2jβ

TE

10

z =

E(x = a , z)

2

| E(x = a , z)|

2

=

|C

TE

10

||1 + Γ L e 2jβ

TE

10

z | =

|C

TE

10

| 1 + |Γ L | 2 + 2|Γ L | cos 2β

TE

10

z + φ L 1/2

Γ L = |Γ L |e jφ L |Γ L | ≤ 1

| E(x = a , z)|

2

z

10 z + φ L 1 / 2 Γ L = | Γ L | e

Γ L = 1

| E(x = a , z)| = 2|C

2

TE

10

| 1 cos 2β

TE

10

z 1/2

2 | C 2 TE 10 | 1 − cos 2 β TE 10 z 1

| E(x = a , z)| z

2

TE

λ g,10

β

TE

10

Γ L = 0

|Γ L | φ L

| Γ L | φ L | E ( x = a , z ) |

| E(x = a , z)| z

2

a

2

| E(x =

, z)| z E max E min |Γ L |

E max E min

=

E max

E

min

=

1 + |Γ L |

1 − |Γ L

| ⇒ |Γ L | = 1

+ 1

d min φ L

TE

d min λ g,10

2β

TE

10

d min + φ L = π φ L = π + 4πd min

λ

TE

g,10

mn

ρ ∂ρ ρ ∂h z

1

∂ρ

+

1 2 h z

ρ 2 ∂ϕ 2

+k

+ k

2

c

h z = 0

∂h z

∂ρ

ρ=a

= 0

2 + k 2 c h z = 0 ∂h z ∂ρ ρ = a =

h z,mn (ρ, ϕ) = B

TE

mn

J m q

mn ρ

a

cos

m = 0, 1, 2,

n = 1, 2, 3

dJ m

dx

x=q

mn = 0 J m m

c,mn 2 = q

mn

a

k TE

2

β

TE

mn =

ω 2 q

c

a

mn

2

mn

mn c

TE c,mn = q

f

2πa

∂ρ ρ ∂e z

1

ρ

∂ρ

+

1

2 e z

ρ 2 ∂ϕ 2

+ k

2

c

e z = 0

e z ] ρ=a = 0

e z,mn (ρ, ϕ) = B

TM

mn

J m q mn ρ

a

m = 0, 1, 2,

J m (q mn ) = 0

cos

n = 1, 2, 3

k TM

c,mn 2 = q mn

a

2

β

TM

mn

=

ω

c

2 q mn

a

2

TM c,mn = q mn c

f

2πa

01

f c2 = f

= 1,306

f c1

f c2

11 f c1 = f

TE

c,11

= 1,841c

2πa

TM

c,01

2,405c

2πa

=

2,405

1,841

f c1 =

f c2 = 2 a > 2b

V

S

V τ n

S

V

• V S V τ n S V ∇ 2 E + ω 2 µ 0

2 E + ω 2 µ 0 0 E = 0 2 H + ω 2 µ 0 0 H = 0

E

H

·

τ S

= 0

· n S = 0

E H

ω 2 µ 0 0

♣ a × b z = 0 z = d + z − z z =

a × b

z = 0

z = d

+z z

z = 0 z = d

d

d =

d

TE

g,mn

2

=

β

TE

mn

ω

TE

mnp

c

2 2

a

b 2 =

2 f

TE

mnp =

c

2

m

a

m, n = 0, 1, 2,

2 + n 2 + p

d

b

2 1/2

m = n

= 0 p = 1, 2, 3,

mnp E z = 0

mnp H z = 0

f

TM

mnp =

c

2

m

a

2 + n 2 + p

d

b

2 1/2

m, n, p = 1, 2, 3,

b < a < d

101

f

TE

101

= c

2

a 2 +

1

1

d

2 1/2

z = 0 z = d

d

n, p = 1 , 2 , 3 , b < a < d 1 0

d =

TE

g,mn

2

=

β

TE

mn

ω

TE

mnp

c

2 q

mn

a

2

d 2 f

TE

mnp =

c

2

q πa

mn

m = 0, 1, 2,

2 + p

d

2 1/2

n, p = 1, 2, 3,

=

mnp E z = 0

mnp H z = 0

f

TM

mnp =

c

2

q mn πa

2 + p

d

m = 0, 1, 2,

2 1/2

n, p = 1, 2, 3,

2a < d

111

f

TE

mnp =

c

2

1,841 πa

2 +

1

d

2 1/2

d d

d E max d E max f f λ g,mn f c,10

f f λ g , m n f c , 1 0 ♣ TE TE

TE

TE

f 0 AB

= f 2 f 1

f 0 AB = f 2 − f 1 AB f 0 f 1 < f

AB

f 0

f 1 < f 0 f 2 > f 0

f 0 Q = 1/AB Q > 10000 AB < 10 4